Clinical Effectiveness of Rivastigmine Monotherapy and Combination Therapy in Alzheimer's Patients. (4th December 2012) - Sonali, Nirmal; Tripathi, Manjari; Sagar, Rajesh; Velpandian, Thirumurthy; Subbiah, Vivekanandhan
Summary Background Rivastigmine is an acetylcholinesterase inhibitor; the genotype data seen alongside the phenotype data explain the mutation or the molecular genetics involved and also help to relate the phenotype of an individual with their genotype. Aim To determine the clinical effectiveness of CYP2D6, CYP3A4, CYP2C9/19, and UGT polymorphism on the steady‐state plasma concentrations and therapeutic outcome of rivastigmine monotherapy and combination therapy in patients with Alzheimer's disease. Result In this study, a significant allele frequency was observed for CYP2D6*3 polymorphism in patients under rivastigmine combination therapy (A>del = 0.50 [patients] and A>del = 0.20 [controls]), UGT2B7 (T = 0.17 [patients] and 0.33 [Controls], and UGT1A9*5 A = 0.58 [patients] and 0.26 [Controls]). The drug levels and P value of responders/nonresponders were found to be 0.17 ± 0.08/0.22 ± 0.16 and 0.574 for rivastigmine and 0.18 ± 0.11/0.66 ± 0.63 and 0.009 for rivastigmine in combination therapy and 1.40 ± 0.65/0.59 ± 0.84 and 0.05 for memantine in combination therapy. Conclusion Poor metabolizer subjects of UGT2B7 polymorphism in patients under rivastigmine combination therapy have higher drug levels with a poor response to the drug treatments.